Associations Between the Dopamine D4 Receptor and DAT1 Dopamine Transporter Genes Polymorphisms and Personality Traits in Addicted Patients - Chmielowiec, Jolanta; Chmielowiec, Krzysztof; Suchanecka, Aleksandra; Trybek, Grzegorz; Mroczek, Bożena; Małecka, Iwona; Grzywacz, Anna (International journal of environmental research and public health, 2018)
Many factors are involved in addiction. The dopaminergic system is thought to be the key element in this process. The mesolimbic dopamine system is a crucial element in the reward system. Changes in this system are thought to be leading to substance use disorders and dependence. Therefore, for our study we chose an analysis of two polymorphisms in genes (Variable Number of Tandem Repeats in DRD4 and DAT1) responsible for dopaminergic transmission, which might be implicated in the scores of personality traits measured by the NEO-FFI test. The study group consisted of 600 male volunteers—299 addicted subjects and 301 controls. Both groups were recruited by psychiatrists; in the case group addiction was diagnosed; in the controls a mental illness was excluded. In both groups the same psychometric test and genotyping by the PCR VNTR method were performed. The results were investigated by a multivariate analysis of the main effects ANOVA. In the presented study no DRD4 main effects were found for any of the analyzed traits but the DRD4 main effects approximated to the statistical significance for the extraversion scale. However, no DAT1 main effects were found for any of the analyzed traits but the DAT1 main effects approximated to the statistical significance for the agreeability scale.These associations open new possibilities for addiction research.